Evolution Characteristics and Mechanism of the Load/Unload Response Ratio Based on Strain Observation Before the Jiuzhaigou MS7.0 Earthquake - Yue, Chong; Ji, Ping; Wang, Yali; Yu, Huaizhong; Cui, Jin; Yu, Chen; Ma, Yuchuan (Frontiers in Earth Science, 2022)
Strain observation is the most intuitive observation equipment to monitor stress change in the crust. Strain equipment near the epicenter area of the Jiuzhaigou earthquake (JZGEQ) provides a lot of reliable pre-seismic and post-seismic data for the study of stress change. In this study, the load/unload response ratio (LURR) method is used to study the stress state of rocks by calculating the ratio of strain observation during the loading phase and unloading phase. Results show that the LURR method based on strain observation is an effective method to describe the dynamic change of the constitutive relationship of the rocks in the crust. Different from the strain observation, the LURR anomaly evolution process is more continuous regardless of the time series curve or spatial and temporal distribution characteristics. The LURR curves of different stations begin to increase above 1.0 gradually from 6 months to 1 year prior to the occurrence of the JZGEQ, reaching the maximum value in 1–3 months before the JZGEQ, and subsequently return to a low level. The maximum value of the LURR anomalies decreases with the distance from the epicenters. At the same time, the spatial and temporal evolution characteristics of the LURR anomalies show us the process of “extension—enhance—weaken” in the epicenter of JZGEQ and its peripheral area prior to the earthquake. The concentration areas of the aforementioned LURR anomalies are all distributed in the pre-seismic normal stress-loading zone, which indicates that the faults are in the process of decoupling, and microfracture may exist in the stage of rock dilatancy.